Single-leg power output and between-limbs imbalances in team-sport players: Unilateral versus bilateral combined resistance training - Gonzalo-Skok, O.; Tous-Fajardo, J.; Suarez-Arrones, L.; Arjol-Serrano, J. L.; Casajús, J. A.; Mendez-Villanueva, A. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To compare the effects of unilateral and bilateral resistance training on single-leg power output, between-limbs imbalance (BLI), bilateral deficit (BLD), change of direction (COD), and linear sprinting and jumping performance in young elite basketball players.